2016
DOI: 10.1007/s11999-015-4509-1
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty After Acetabular Fracture Is Associated With Lower Survivorship and More Complications

Abstract: Background Despite modern fracture management techniques allowing for near anatomic reduction of acetabular fractures, there continues to be a risk of posttraumatic arthritis and need for total hip arthroplasty (THA). Few well-controlled studies have compared THA after acetabular fractures with THAs performed for other indications in terms of survivorship or complications, and none, to our knowledge, present 10-year survivorship data in this setting. Questions/purposes (1) How does the 10-year survival of THA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 18 publications
(27 reference statements)
4
67
0
9
Order By: Relevance
“…Other authors have not confirmed these excellent results, i.e. Morrison showed a 10-year survival rate of 70% for uncemented acetabular components [26]. A review from 2014 could not show statistically significant differences in survival between cemented and uncemented components [20].…”
Section: Introductionmentioning
confidence: 93%
“…Other authors have not confirmed these excellent results, i.e. Morrison showed a 10-year survival rate of 70% for uncemented acetabular components [26]. A review from 2014 could not show statistically significant differences in survival between cemented and uncemented components [20].…”
Section: Introductionmentioning
confidence: 93%
“…No clear consensus can be found in the literature on which technique is preferable, and good results are found for all alternatives 90,97,98 . Compared to THA for non-traumatic OA the outcome is, however, notably worse and the complication rate higher 98,99 .…”
Section: Salvage After Failed Treatmentmentioning
confidence: 99%
“…THA after post traumatic arthritis or avascular necrosis associated with acetabular fractures, will markedly improve patients' quality of life 88,89,156 , but it is associated with a higher rate of complications, reduced long time survival 90,98,99 and less improvement on patients symptoms 157,158 compared to a primary total hip replacement. In fact, the results after secondary THA in acetabular fractures are similar to that of revision arthroplasty 159,160 .…”
Section: Secondary Total Hip Replacementmentioning
confidence: 99%
“…Morison et al .,48 however, found higher rates of survival in the PTOA group (70% vs. 90%) and when only considering aseptic loosening – 77% versus 90%. Complication rates are higher in the PTOA group, equivalent to revision procedures,28 and Morison et al 48. had an infection rate of 7% in their PTOA group versus no infections in DOA group – they noted previous fixation was a risk for infection.…”
Section: Resultsmentioning
confidence: 92%